IMPLEMENTASI METODE RONDO UNTUK MENINGKATKAN TEKNIK PASSING MAHASISWA PADA MATA KULIAH FUTSAL PENJAS PRODI PENJAS FKIP UNIB - Sugiyanto Sugiyanto; Bogy Restu Ilahi; Defliyanto defliyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2019)
This study aims to find out how the Implementation of the Rondo Method to Improve Student Passing Techniques in Futsal Courses so as to improve the learning quality of seventh semester students in Class A Penjas Study Program FKIP Unib. Through the rondo method students are included in groups to practice passing. The hope is that students have an active and contributive attitude so that getting meaningful learning both individually and in groups and improving the quality of learning in Futsal courses is achieved. The subjects of this study were seventh semester students of class A Penjas Study Program FKIP UNIB who were taking the Futsal Orpil course. Data collection techniques were carried out by means of tests conducted at the beginning and at the end of the cycle, there was an increase in the skills of basic passing techniques before and after using the rondo method in the first cycle, which proved to be an increase of 50% of 20 students who received complete grades from 40 students based on details percentage value (A) 12 people, (B) 8 people, (C) 20 people using the rondo method with 1 person being a guard. In cycle II there was an increase in passing skills in the rondo futsal game method with 2 students who became guards. Evident from the results of the study with the results of a 65% increase in completeness from the first cycle which only 50% completed from 40 students with details of the value (A) 16 people, (B) 9 people, (C) 15 people. There was an increase from the first cycle, namely 15% increase with completeness from 20 students to 26 students who completed Futsal learning.